Hubungan Tingkat Pengetahuan terhadap Outcome Klinik Pasien Diabetes Melitus Tipe 2 - Laksmy Anggun Larasati; Tri Murti Andayani; Susi Ari Kristina (Faculty of Pharmacy, Universitas Gadjah Mada)
Diabetes is a chronic disease that requires good therapeutic management and self care to achieve optimal glycemic target. The important barrier to achieve good glycemic control is a lack of knowledge about optimal glycemic targets. The purpose of this study was to determine the relationship of the level of knowledge to clinical outcome of type 2 diabetes mellitus in Yogyakarta and Bantul primary health care. This was an observational study with a cross sectional design. The sampling technique was done by accidental sampling for patients visiting the primary health care from October to December 2018 that involved 200 type 2 diabetes mellitus patients who were included in the inclusion criteria. The level of knowledge was measured by the Diabetes Knowledge Questionnaire (DKQ)-24 which had 24 questions and the clinical outcome was obtained from laboratory measurement data as well as from medical record data when the patient was in routine control. Sociodemographic data were analyzed descriptively. The relationship between the level of knowledge and clinical outcomes was analyzed using chi square. The results showed that the knowledge level score had an average value of 12. The most incorrect answer was in etiology and diabetes self care, which is eating too much sugar and sweet foods is the cause of diabetes (97%), exercise regularly increasing the need of hormone insulin or diabetes medication (82%), the insulin reaction is caused by too much food (84%) and diabetics should clean the wound with betadine and alcohol (88%). There were 106 (53%) patients who achieved good glycemic control. Chi square test showed no relationship between the level of knowledge of clinical outcomes (p = 0.328). The result of this study may become a material and education content evaluation in diabetic patients.